Comparing the accuracy of Pipelle versus hysteroscopy and curettage in the diagnosis of chronic endometritis in women with recurrent implantation failure: A prospective cross-sectional study - Elaheh Pahlevan Falahy; Mohammad-Taha Pahlevan-Fallahy; Fatemeh Keikha (PLoS ONE, 2025)
Objectives Chronic endometritis (CE) is defined as chronic inflammation in the endometrium; when treated, implantations significantly improve. The standard test for CE confirmation is an endometrial biopsy, but the appropriate sampling method needs to be clarified. We conducted this study to compare pipelle biopsy and hysteroscopy with curettage. Study design This is a prospective cross-sectional study with all (40 patients) RIF patients under 40 referred to our tertiary center between December 2021, and December 2022 who underwent pipelle biopsy and hysteroscopy with curettage between days twelve to fifteen of their menstruation cycle. We then compared the diagnostic accuracy, demographics, and previous IVF history between the CE and non-CE groups. Results Patients had a mean age of 34 ( ± 5.4) years and BMI of 25.8 ( ± 3.6). Thirteen patients (32.5%) were diagnosed with CE. There was no significant difference between CE and non-CE groups regarding maternal or paternal age, BMI, number of IVFs and embryos, and interval from the last IVF. Pipelle biopsy had 100% accuracy for CE diagnosis, while hysteroscopy with curettage had a sensitivity of 92.3% (95% CI: 77.8% - 100%) and specificity of 100%. Based on McNemar’s test, the two sampling methods had no significant difference (P = 1.0 and 0.317, respectively). Conclusion There is no significant difference between the two methods in the diagnosis accuracy of CE in RIF patients. Since pipelle is more cost-effective and has fewer complications than hysteroscopy with curettage, pipelle biopsy may replace curettage for CE diagnosis.